2016
DOI: 10.1177/0956462416638609
|View full text |Cite
|
Sign up to set email alerts
|

Shigellosis in men who have sex with men: an overlooked opportunity to counsel with pre-exposure prophylaxis for HIV

Abstract: In the absence of other epidemiological exposures, shigellosis in men who have sex with men (MSM) suggests engagement in high-risk sexual encounters. Infection and diagnosis of shigellosis in MSM presents a potentially overlooked opportunity to discuss the availability of pre-exposure prophylaxis medications to prevent incident HIV infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…However, resistance profiles differed across groups at risk for shigellosis; 42 of the 43 domestically acquired DSA-Shigella cases in Minnesota occurred among men, 60% of whom were also infected with HIV. This trend has been observed in other jurisdictions and has implications for clinical testing, public health surveillance, case management, and prevention efforts (27)(28)(29).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, resistance profiles differed across groups at risk for shigellosis; 42 of the 43 domestically acquired DSA-Shigella cases in Minnesota occurred among men, 60% of whom were also infected with HIV. This trend has been observed in other jurisdictions and has implications for clinical testing, public health surveillance, case management, and prevention efforts (27)(28)(29).…”
Section: Discussionmentioning
confidence: 62%
“…General shigellosis prevention messages, such as avoiding certain activities such as preparing food for others and swimming while ill, should also be included. In addition, because of the high prevalence of HIV and recent STDs among men with shigellosis, clinicians might use a diagnosis of shigellosis in a man as a reason for HIV and STD screening and use HIV or STD diagnoses to counsel about prevention of shigellosis and other sexually transmitted enteric infections (29). Because patients could seek care from clinicians working with MSM in the context of STDs or general practitioners who might not provide treatment for STD patients, cross-training is needed to educate providers for prevention of shigellosis and potential indicators for STD risk.…”
Section: Discussionmentioning
confidence: 99%
“…BTRC (Beta-Transducin Repeat Containing E3 Ubiquitin Protein Ligase) is a protein coding gene. The protein encoded by BTRC is a member of the F-box protein family and disease associated with BTRC is Shigellosis [83]. Based on our analysis result, it was found that the expression of MKI67 , DLG2 and BTRC might be regulated by miR-4723-3p.…”
Section: Discussionmentioning
confidence: 87%
“…Of the 39 studies included in this review, five did not describe any AMR to azithromycin, ciprofloxacin or ceftriaxone. 13,22,27,28,35 These included: a case report of a fully sensitive isolate of Shigella flexneri 2a; a case report where susceptibility testing identified the organism as sensitive to ciprofloxacin, gentamicin and co-amoxiclav, but resistant to ampicillin, streptomycin, tetracyclines, sulphonamides and doxycycline; a case report of an isolate of S. flexneri 2a with ampicillin and co-trimoxazole resistance and two cases series with variable resistance to amoxycillin, co-trimoxazole, and nalidixic acid.…”
Section: Resultsmentioning
confidence: 99%